Hidden costs of control: Three repetitions and an extension - Matteo Ploner; Katrin Schmelz; Anthony Ziegelmeyer (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
We report three repetitions of Falk and Kosfeld's (2006) C5 and C10 treatments whose results largely conflict with those of the original study. We mainly observe hidden costs of control of low magnitude which lead to low-trust principal-agent relationships. We also report an extension where performance-based rewards are absent i.e. both principals and agents are paid according to a at participation fee. Our extension largely reproduces the striking findings of the original study. In particular, we observe that hidden costs outweigh benefits of control.
Keywords: C81; C91; M52; 330; Control; Experimental Economics; Incentives; Intrinsic Motivation; Trust; Leistungskontrolle; Leistungsanreiz; Motivation; Vertrauen; Test